Linguistics Learning Style as Innovation: The Successful of English Foreign Language Students - Sari, Ima Frafika (Institut Agama Islam Negeri Ponorogo, 2023)
This research aims at revealing: the characteristic of the learning style for EFL; the advantages of the learning style for EFL; the innovation of the learning style for EFL. It is a kind of descriptive qualitative research aimed at revealing the linguistics learning style as an innovation for the English Foreign language. Linguistics learning research is still insufficient as an innovation for EFL; therefore, this research is significant to be conducted. The finding of the research can be described as follows: First, there are nine learning styles, namely; visual learning, auditory numerical, social group, visual numerical, kinesthetics, expressiveness oral, auditory language, social individual and expressiveness written. Second, the beneficial of linguistics learning are improved language skills, better comprehension, increased engagement, flexibility, and better communication skills. Third, the innovations of learning style in EFL include language learning apps, interactive language learning platforms, AI-assisted language learning, social media use, multimedia-based learning, and content-based instruction.